2021
DOI: 10.1186/s40359-021-00651-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of household chaos and parental responsiveness on child executive functions: a novel, multi-method approach

Abstract: Background Executive functions can be adversely affected by contextual risks in the home environment including chaos and parenting challenges. Furthermore, household chaos negatively influences parenting practices. Few studies, however, have examined the role of parenting in the association between household chaos and child executive functions. Methods Using a sample of 128 school-aged children (mean = 61.9 months, SD = 2.0, range 58–68 months) and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 85 publications
(113 reference statements)
3
9
0
Order By: Relevance
“…Regression analyses indicated that mothers’ Negative Reactions accounted for a significant proportion of the variance in Inhibitory Self-Control (for both mothers and teachers), Flexibility (only for mothers), and Emergent Metacognition (for both mothers and teachers) indexes. Although this seems to be the first study to assess links between parental emotional responsiveness and children’s EF, these findings are consistent with previous studies supporting the role of caregivers in children’s EF (e.g., [ 53 , 54 , 82 , 87 , 88 , 89 , 90 , 91 , 92 ]). For example, Bernier and colleagues [ 53 ] proposed that parental responsiveness could promote higher levels of children’s EF by affecting children’s neurobiological structure development and providing a social environment for the child to observe and practice positive regulatory strategies related to EF.…”
Section: Discussionsupporting
confidence: 91%
“…Regression analyses indicated that mothers’ Negative Reactions accounted for a significant proportion of the variance in Inhibitory Self-Control (for both mothers and teachers), Flexibility (only for mothers), and Emergent Metacognition (for both mothers and teachers) indexes. Although this seems to be the first study to assess links between parental emotional responsiveness and children’s EF, these findings are consistent with previous studies supporting the role of caregivers in children’s EF (e.g., [ 53 , 54 , 82 , 87 , 88 , 89 , 90 , 91 , 92 ]). For example, Bernier and colleagues [ 53 ] proposed that parental responsiveness could promote higher levels of children’s EF by affecting children’s neurobiological structure development and providing a social environment for the child to observe and practice positive regulatory strategies related to EF.…”
Section: Discussionsupporting
confidence: 91%
“…This total score reflects the extent of home chaos, with higher scores representing more disorganized, confused, and noisy home environments. The scale has good reliability and validity in previous study (Andrews et al, 2021). The Cronbach's alpha for this scale was 0.81 in the current study.…”
Section: Measures Home Chaos Scalesupporting
confidence: 65%
“…Still, it is unclear as to whether the CHAOS questionnaire is robust enough to measure household chaos from an adolescent’s perspective. Additionally, the CHAOS tool focuses mainly on the disorganization dimension of this construct and less so on the instability dimension [ 15 , 17 ]. Some authors, based on the need to better capture the chaos construct and its subdomains, have argued in favor of using a more comprehensive household chaos measurement approach, notably to better capture the instability dimension [ 15 ], to include measurements of specific family routines [ 8 ], and to rely on systematic observations (e.g., direct observations and home tours) [ 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the CHAOS tool focuses mainly on the disorganization dimension of this construct and less so on the instability dimension [ 15 , 17 ]. Some authors, based on the need to better capture the chaos construct and its subdomains, have argued in favor of using a more comprehensive household chaos measurement approach, notably to better capture the instability dimension [ 15 ], to include measurements of specific family routines [ 8 ], and to rely on systematic observations (e.g., direct observations and home tours) [ 15 , 17 ]. Studies where specific family routines are assessed (e.g., sleep and meal-time routines and screen time limits) as indicators of household organisation, have reported a statistically significant associations with child overweight [ 8 ].…”
Section: Discussionmentioning
confidence: 99%